2014
DOI: 10.1111/ene.12539
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25‐hydroxyvitamin D and cognitive decline in the very old: the Newcastle 85+ Study

Abstract: Background and purposeStudies investigating the association between 25-hydroxyvitamin D [25(OH)D] and cognition in the very old (85+) are lacking.MethodsCross-sectional (baseline) and prospective data (up to 3 years follow-up) from 775 participants in the Newcastle 85+ Study were analysed for global (measured by the Standardized Mini-Mental State Examination) and attention-specific (measured by the attention battery of the Cognitive Drug Research test) cognitive performance in relation to season-specific 25(OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 48 publications
1
66
1
1
Order By: Relevance
“…Increasing the behavioral and cognitive function would increase outdoor activities and exposure to sunlight [1,48]. Different studies had reported that insufficiency or deficiency of vitamin D is associated with cognitive impairment [1,23,[53][54][55][56]. Vitamin D deficiency can be associated with muscle weakness that might lead to cognitive impairment [57].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the behavioral and cognitive function would increase outdoor activities and exposure to sunlight [1,48]. Different studies had reported that insufficiency or deficiency of vitamin D is associated with cognitive impairment [1,23,[53][54][55][56]. Vitamin D deficiency can be associated with muscle weakness that might lead to cognitive impairment [57].…”
Section: Discussionmentioning
confidence: 99%
“…The median (interquartile range) plasma vitamin B 12 was 232 (170-324). Roughly 17 % (n 125) were below the threshold of 148 pM/l for plasma vitamin B 12 and, 15·0 % (n 110) were above 15 µM/l for homocysteine while being deficient for cobalamin (N Mendonҫa et al, unpublished results). The NDNS rolling programme estimated that 5·9 % were below 150 pM/l of serum vitamin B 12 (66) .…”
Section: B-vitamin Statusmentioning
confidence: 99%
“…for those who are housebound) and low vitamin D status contributes to the risk of mortality (11) , cognitive decline (12) , several age-related diseases and low mood and depression (13) . Vitamin B 12 uptake from the gut is impaired in those with atrophic gastritis (a common problem in older people (14) and vitamin B 12 deficiency can damage the nervous system leading to balance disturbances and, possibly, more rapid cognitive decline. However, a recent intervention study (B-PROOF study) reported no effect of a combined supplement of folic acid and vitamin B 12 on cognitive outcomes among older (mean age 74·1 years) Dutch participants (15) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
See 2 more Smart Citations